2015
DOI: 10.1080/21501203.2015.1075232
|View full text |Cite
|
Sign up to set email alerts
|

Macrofungal diversity in community-managed sal (Shorea robusta) forests in central Nepal

Abstract: Macrofungi constitute a group of the high-value forest resources worldwide. In this paper, we report species richness and composition of the macrofungi in sal (Shorea robusta) forests of mid-hill central Nepal, which were managed for 4–29 years by the local communities. The sal forests were rich in macrofungi (115 species) with Polyporaceae being the largest family followed by Clavariaceae. Saprotrophic fungi were more common than mycorrhizal species. The proportion of mycorrhiza was <40% of the total macrofun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…This suggests that the presence of both cultivated lands and fallow in a landscape will increase the regional diversity of edible mushrooms. This is contrary to some findings (Andrew et al, 2013;Baral et al, 2015;Adeniyi et al, 2018) that human interference through cultivation leads to decline in the species richness and abundance of mushrooms in general. However, more species diversity was in the fallow than the cultivated lands, hence in the complete absence of fallow mushroom diversity will greatly decline.…”
Section: Mushroom Distribution According To Microhabitatscontrasting
confidence: 90%
“…This suggests that the presence of both cultivated lands and fallow in a landscape will increase the regional diversity of edible mushrooms. This is contrary to some findings (Andrew et al, 2013;Baral et al, 2015;Adeniyi et al, 2018) that human interference through cultivation leads to decline in the species richness and abundance of mushrooms in general. However, more species diversity was in the fallow than the cultivated lands, hence in the complete absence of fallow mushroom diversity will greatly decline.…”
Section: Mushroom Distribution According To Microhabitatscontrasting
confidence: 90%
“…Bio-physical variables, such as tree canopy cover, litter cover and anthropogenic disturbances A detailed sampling of macrofungi diversity was made by applying systematic random method during June/July 2016, where plots were laid in each forest type with a minimal variation in elevation (15001600 m asl). A total of 20 plots were laid in each forest types along four transects, maintaining inter-plot distance of at least 20 m (Baral et al 2015). Presence/absence data of macrofungal species was recorded in each plot.…”
Section: Field Samplingmentioning
confidence: 99%
“…(a) observation made by Baral et al (2015) in central Nepal. Sysouphanthong et al (2010) also reported higher macrofungal diversity in forests having higher canopy closure.…”
Section: Ion Ngal Richness and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The checklist of mushroom species provided can be used for future related research aimed at conservation. Many researchers note that human interference through deforestation, urbanization, cultivation, etc., lead to decline in species richness and the abundance of mushroom species (Egli 2011, Andrew et al 2013, Baral et al 2015, Adeniyi et al 2018). However, this study revealed that some human activities contribute positively to mushroom diversity in this area, which belongs to a savanna region.…”
Section: Implication For Conservation Of Mushroom Diversitymentioning
confidence: 99%